Birth weight and term of the gestation in pregnancies complicated by isolated oligo and isolated polyhydramnios - Reddy V, Manikanta; S, Senthil Kumar; N, Sanjeeva Reddy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To access the birth weight of the newborn and term of the gestation in pregnancies complicated by isolated oligo and polyhydramnios. Methods: A Hospital based study has been conducted in the Department of Obstetrics and Gynaecology, Sri Ramachandra Medical College and Research Institute, Chennai. All the singleton pregnancies diagnosed with Isolated Oligo and Polyhydramnios were enrolled in the study. All the subjects were followed up to their delivery. Birth weight and Term of the Gestation were recorded immediately after delivery. Results: Out of 3,567 patients 32 (0.9%) and 5 (0.15%) were diagnosed as Isolated Oligo and Polyhydramnios respectively. Among 32 (0.9%) newborns of Isolated Oligohydramnios, 5 (15.62%) were Very Low Birth Weight (< 1,500gms), 14 (43.75%) were Low Birth Weight (1,500 – 2,500gms) and 13 (41%) were with normal birth weight (2,500 - 3,800gms). None of the cases were with Large for Gestational Age babies (> 3800gms). On the other hand Preterm and Term gestations were 17 (53.12%) and 15(46.8%) respectively in this group. Among the 5 (0.15%) cases of Isolated Polyhydramnios group, Very Low Birth Weight and Low Birth Weight newborns were 1(20%) each and newborns with normal Birth weight were 3 (60%). Similarly, Preterm and Term gestations were 2(40%) and 3(60%) respectively. Conclusion: Isolated Oligo and Polyhydramnios are associated with increased rate of Low Birth Weight (Very Low Birth Weight and Low Birth Weight) neonates and Preterm deliveries.